Conserved domains and structural motifs that differentiate closely related Rex1 and Rex3 DEDDh exoribonucleases are required for their function in yeast - Peter W. Daniels; Sophie Kelly; Iwan J. Tebbs; Phil Mitchell (PLoS ONE, 2025)
The DEDD family of exonucleases has expanded through evolution whilst retaining a conserved catalytic domain. One subgroup with closely related catalytic DEDD domain sequences includes the yeast enzymes Rex1 (RNA exonuclease 1) and Rex3, the metazoan REXO1 (RNA exonuclease 1 homologue) and Rexo5 proteins, and the plant protein Sdn5 (small RNA degrading nuclease). Comparison of protein structure models and sequence analyses revealed that this group can be differentiated into two distinct clades consisting of Rex1, Rexo5 and Sdn5 on the one hand, and Rex3 and REXO1 on the other. The catalytic domain of Rex1-related proteins is inserted within a conserved, discontinuous alkaline phosphatase (AlkP) domain. The AlkP domain of yeast Rex1 contains three surface loops that are modelled to be directed towards the DEDD domain, one of which forms an extended helical arch that is found in homologues across fungi and plants. We show that this arch and an adjacent loop are required for Rex1-mediated processing of 5S rRNA and tRNA in Saccharomyces cerevisiae . Rex3-related proteins, including REXO1, lack the AlkP domain but contain a KIX domain (CREB kinase-inducible domain (KID) interacting domain) and a cysteine- and histidine-rich domain (CHORD) adjacent to a C-terminal DEDD domain. Deletion of the N-terminal region within yeast Rex3 spanning the KIX domain blocked its function in RNase MRP processing. In contrast to Rex1, Rex3 proteins are found in metazoans and fungi but not in plants or algae. This work identifies evolutionarily conserved structural hallmarks within Rex1 and Rex3 proteins and demonstrates that specific features are required for Rex1- and Rex3-mediated RNA processing pathways in vivo.